CELLULAR AND MOLECULAR IMPACT OF THE MELANOCORTIN RECEPTOR AGONIST PL8177 IN DEXTRAN SODIUM SULFATE (DSS)-INDUCED COLITIS IN RATS. (22nd January 2022) - Dhingra, Priyanka; Obr, Alison; Spana, Carl; Dodd, John; Kayne, Paul
Abstract: INTRODUCTION: The melanocortin 1 receptor (MC1r)–specific agonist PL8177 and its main metabolite PL8435 have demonstrated MC1r binding affinity and functional activity that mirrors that of α-melanocyte stimulating hormone (a-MSH). a-MSH has been demonstrated to be effective in reducing inflammation in numerous experimental models. This study investigates the effects of PL8177 on inflammation, cell population composition, and gene and protein expression in colons from a DSS–induced rat model of colitis. The objective is to determine the effectiveness of PL8177 in this model and to characterize its underlying mechanism of action. METHODS: Male Wistar rats received 5% DSS in drinking water for 3 days to induce colitis. Rats in the sham group received drinking water only (each group n=6). The other groups received vehicle control (placebo)–filled capsules; PL8177-filled capsules at 20, 50, and 100 μg/animal (by oral gavage); or oral mesalazine (positive control). At termination on day 8, 24 hours after the last dosing, colon tissues were harvested, dissected and snap frozen with liquid nitrogen. Colon samples were analyzed for cytokine levels, single nuclei RNA-seq, and data-independent acquisition tandem mass spectrometry (LC/MS DIA). Colitis was assessed by a disease activity index (diarrhea and rectal bleeding), colon length shortening, colon weight gain, and histopathological assessment. The total colitis index, was used to assess inflammatory damage. RESULTS: Colitis was induced in rats treated with DSS. Oral PL8177 50 μg/animal treatment showed a significant improvement in colon weight (53% reduction), stool consistency, and fecal occult blood score compared to vehicle. There was a significant ( P <0.05) improvement in the total colitis index for the PL8177 100-μg group vs vehicle control group. All PL8177-cohorts showed greater improvement in the total colitis index compared to the mesalazine-treated cohort. PL8177 50 μg/animal showed a significant improvement in colon weight (53% reduction), while mesalazine treatment was associated with significant reduction in colon length, but only moderate improvement (35%) in colon weight. Changes in the cellular population compositions, gene expression changes and protein level data will be presented and discussed at the conference. CONCLUSION: Oral PL8177 treatment of inflamed colon showed significant improvement in markers of colitis in the rat model compared to the placebo and mesalazine control groups supporting the aim of treating inflammatory bowel disease in humans. Genomic and proteomic data will be interpreted in the context of disease change to identify alterations in immune and cellular states of the experimental colons.